Análisis energético en el proceso de fundición del aluminio en el horno del Instituto Superior Tecnológico Cotopaxi. - Morales Cevallos, José Williams (2021)
The present research project consisted of analyzing the heat losses in the aluminum smelting process using two crucible furnaces of different types of refractory material, these furnaces have equal dimensions, capacity and heat source, the first crucible furnace was designed in its three side walls and a roof type wall with red brick as thermal insulation and a metal cover, has an opening of 0.25 m2, that is, an open side wall, for which it requires an amount of 38,016 kW to carry out the process of aluminum smelting, considering the heat losses by conduction of 8256 W, by convection 195.44 W and by opening 18.65 kW generating a total loss of 27.136 kW, this furnace melts 7 kg of aluminum in a time of 20 minutes, so the heat supplied by the furnace is 66.66 kW giving a yield of 42.97%, meanwhile, crucible furnace No. 2 presents in its 3 side walls and a roof-type wall two refractory brick linings that in the middle contain a layer of ceramic blanket, additionally in the fourth side wall a metal gate was implemented, resulting in the amount of heat of 14.69 W needed to melt 7 kg of aluminum where the conduction losses are 2915.03 W and the convection losses are 131.11 W, the opening losses are negligible, and the crucible furnace supplies 74.07 kW of heat energy at a melting time of 18 minutes, resulting in a yield of 80.16%.